Menyikapi Fenomena Pakaian Uniseks: Kontekstualisasi Makna Hadis Larangan Berpakaian Menyerupai Lawan Jenis - Lubis, Manahara Alamsyah (Journal of Hadith Studies, 2024)
The interpretation of hadiths prohibiting cross-dressing, as found in classical sharḥ (commentary) literature, is limited to specific distinctions between male and female clothing and is no longer fully relevant to the contemporary phenomenon of unisex fashion. This article offers a contextualized rereading of the hadith using Fazlur Rahman’s double movement approach to uncover a more relevant moral meaning. It explores: (a) how classical sharḥ literature interprets the hadith; (b) the underlying considerations shaping those interpretations; and (c) how the hadith can be recontextualized in light of current fashion trends. Through qualitative library-based research, this study reveals that classical commentaries do not provide an interpretation that corresponds to the concept of unisex fashion, due to the absence of such a phenomenon in early Islam and the strong emphasis on gender identity. In today's context, which places a high value on aesthetics, the newly contextualized meaning suggests that wearing unisex clothing is not prohibited as long as the boundaries of gender identity remain clear.